Tax compliance, corruption and deterrence: An application of the slippery model. - Carvalho, Daniela (2014)
Tax evasion has been a common problem in some countries with damaging consequences to national budgets. It is thus important to understand what informs attitudes towards tax compliance. Trust, perceptions of fairness and corruption have consistently been found to play a crucial role in compliance behaviour. However, research findings have been inconsistent regarding the use of deterrence power to discourage tax evasion. The current study aims at examining the influence of perceived fairness and corruption plus sanctions used by authorities to enforce tax compliance attitudes with a sample of Portuguese economics and management students (N= 330). Findings suggest that trust in authorities and their capacity to deter and punish tax evaders are interrelated and that both are important in securing tax compliance. Findings are discussed in the current Portuguese context.